ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI DI KELURAHAN PAJINTAN KECAMATAN SINGKAWANG TIMUR KOTA SINGKAWANG - margareta anggi; Josua Parulian Hutajulu; Anita Suharyani (Fakultas Pertanian Universitas Janabadra, 2025)
Due to land conversion, there is less land available for rice, a product that is crucial to the country's food security. Rice productivity is declining as a result of this situation, particularly in Pajintan Village, East Singkawang District, Singkawang City, where most farmers manage small plots of land for meager pay. Using a survey method on 76 farmers who were specifically chosen and analyzed using multiple linear regression using SPSS version 25, this study aims to investigate the impact of land area, urea fertilizer seeds, phonska fertilizers, pesticides, and labor on rice production. It found that the majority of respondents were women between the ages of 46 and 55 who were classified as productive age, had only completed elementary school (53.95%), had only 1–10 years of farming experience, and managed, and managing narrow land <0.5 ha. The study using multiple linear regression illustrates that the seed variable has a positive and significant impact on lowland rice production, while land area, urea fertilizer, and labor have a negative and significant impact on lowland rice production. Based on the evaluation of the adjusted R2 of 0.380, it shows that the model is only able to explain 38% of the production variation, while the rest is influenced by other factors outside the model, such as irrigation conditions, weather, and limitations in farm management. This finding indicates the importance of managing production factors, especially the use of quality seeds, the use of appropriate fertilizers, and labor efficiency in increasing lowland rice production.